The Drosophila Broad-complex regulates developmental changes in transcription and chromatin structure of the 67B heat-shock gene cluster. - Dubrovsky, E.B.; Dretzen, G.; Bellard, M. (Journal of Molecular Biology, 1994)
At the end of the third larval instar of Drosophila, ecdysone triggers the tissue-specific activation of gene expression. In cytogenetic and molecular studies, the Broad-complex (BR-C) locus has been defined as a key element in the hierarchy of hormonal regulation of gene activity. Here we show that BR-C function is required for the regulation of the small hsp genes, which are clustered in the 67B puff and are known to be activated by heat shock and by ecdysone during development. We have found that the genes of the 67B cluster are expressed differentially in the salivary glands. While hsp23 and hsp27 transcripts accumulate at relatively high levels, those of hsp22 and hsp26 are present at low and intermediate levels, respectively. The complete BR-C deficiency as well as mutations of the npr class reduce the expression of genes hsp23 and hsp27 by 95 to 99%. The analysis of mutants representing two subfunctions of the BR-C-l(1)2Bab and l(1)2Bc, has shown that the latter is principally required for complete hsp induction. As sites of DNase I hypersensitivity in chromatin are believed to correspond to gene regulatory sequences, we have studied the changes of chromatin structure in the 67B region at different states of hsp gene activity. Upon hormonal induction, at the onset of metamorphosis, additional DNase I hypersensitive sites (DHS) appear in the 5' regions, four DHSs are associated with hsp23 and two with hsp27. We suggest that they are due to the binding of the hormone-receptor complex and/or transcription factors, related to ecdysone action. Finally, two DHSs (at -1400 of hsp23 and at -1200 of hsp27) are absent in the mutant nuclei, and thus may correspond to the target sequences for the BR-C-dependent regulatory protein(s).